ENHANCING MARKETING STRATEGY AND ROLE OF COMPLIANCE AND ITS IMPACT ON MONETARY DEVELOPMENT - Salman abed Hadi; Basim Hanoon Jasim; Kawther Jawad Yousif (American Journals, 2024)
Marketing dimensions (Proactiveness-PR, Focus-FO and Innovativeness- IN) are considered a basic activity that works to raise the efficiency of monetary development, which affects Monetary Development (MD) through Compliance (CO) as an intermediary. Marketing strategy works to raise the efficiency of Companies (CO) in multiple ways. In this study, the researcher focuses on obtaining positive, supportive results. In this study, the focus is on the dimensions of marketing (Proactiveness-PR, Focus-FO and Innovativeness- IN), and their impact on Monetary Development (MD) through Compliance (CO) as a mediator. This study also contributed significantly to raising and increasing the profits of institutions. Marketing it is a set of processes or activities that work to discover customers’ desires and develop a group of products or services that satisfy their desires and achieve profits for the organization within an appropriate period of time. It focuses on the importance of the impact of marketing dimensions (Proactiveness-PR, Focus-FO and Innovativeness- IN) on Monetary Development (MD) through employee Compliance (CO) in working within the organization to achieve employee satisfaction. The researcher relies on the most advanced methods in a more effective way. The researcher in this study also identifies the problems facing the organization and finds appropriate solutions to them. The number of the target sample was (160), the error was (4), and the questionnaire was correct (156). The statistical analysis used SPSS & SmarrtPLS 4 and a Likert scale of 7, and the target sample was Al-Tariq Food Products Company/Iraq. The number of results (6) were positive, and (1) was non-positive.
Keywords: Marketing, Proactiveness, Focus, Innovativeness, Compliance, Monetary Development.